Loss of Drosophila E3 Ubiquitin Ligase Hyd Promotes Extra Mitosis in Germline Cysts and Massive Cell Death During Oogenesis - Dorogova, Natalia V.; Galimova, Yuliya A.; Bolobolova, Elena Us.; Baricheva, Elina M.; Fedorova, Svetlana A. (Frontiers in Cell and Developmental Biology, 2020)
The Drosophila hyperplastic disc (hyd) gene is the orthologue of mammalian tumour suppressor EDD, which is implicated in a wide variety of cellular processes, and its regulation is impaired in various tumours. It is a member of the highly conserved HECT family of E3 ubiquitin ligases, which directly attach ubiquitin to targeted substrates. In early works, it was shown that Drosophila Hyd may be a tumour suppressor because it is involved in the control of imaginal-disc cell proliferation and growth. In this study, we demonstrated that Hyd is also important for the regulation of female germ cell proliferation and that its depletion leads to additional germline cell mitoses. Furthermore, we revealed a previously unknown Hyd function associated with the maintenance of germ cells’ viability. A reduction in hyd expression by either mutations or RNA interference resulted in large-scale germ cell death at different stages of oogenesis. Thus, the analysis of phenotypes arising from the hyd deficiency points to Hyd’s role in the regulation of germline metabolic processes during oogenesis.